2022
DOI: 10.1002/cam4.5332
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in cancer survival: Relation to stage at diagnosis, treatment, and centralization of patients to accredited hospitals, 2005–2014, Japan

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Furthermore, as the deprivation index increased, the risk of death also increased. This trend has also been observed in studies conducted in Japan and the United States [ 23 24 ]. However, this finding may differ from that of domestic studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, as the deprivation index increased, the risk of death also increased. This trend has also been observed in studies conducted in Japan and the United States [ 23 24 ]. However, this finding may differ from that of domestic studies.…”
Section: Discussionsupporting
confidence: 76%
“…Notably, for relatively preventable cancers such as cervical cancer, the mortality rate in the low-income group was twice that of the high-income group, whereas disparities in mortality rates for lung and liver cancers were comparatively narrower [ 11 ]. Furthermore, studies from Japan and the United States have found a correlation between measuring SES levels using the regional deprivation index and the risk of cancer mortality [ 23 24 ]. However, a similar relationship was not identified in a Korean study [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an investigation of socioeconomic inequalities in cancer incidence and survival rate is also required to clarify the overall picture of the cancer burden. 29 …”
Section: Discussionmentioning
confidence: 99%